THE ASSOCIATION BETWEEN INCOME STATUS AND DIET DIVERSITY AMONG IIUM KUANTAN STUDENTS - MOHD SAFIEE, NURUL SHAHIDA; MOHAMED NOR, NORAISHAH (International Journal of Allied Health Sciences, 2023)
Introduction: Unhealthy eating patterns are one of the contributing factors that may cause malnutrition or nutrition-related disease in an individual. However, the ability to start a healthy, nutritious, and low energy-dense food is influenced by the individual’s income, especially the budget allocated to food expenditures besides other commitments. Therefore, this study aimed to determine the relationship between income level and diet diversity among students in IIUM Kuantan. Methods: A total of 107 respondents were chosen through proportionate stratified sampling from each Kulliyyah available in IIUM Kuantan: Kulliyyah of Allied Health Sciences (KAHS), Kulliyyah of Medicine (KOM), Kulliyyah of Pharmacy (KOP), Kulliyyah of Dentistry (KOD), Kulliyyah of Sciences (KOS) and Kulliyyah of Nursing (KON). Participants were interviewed using a structured questionnaire to obtain information on their socio-demographic characteristics, nutrient intake, and dietary diversity. A questionnaire with three sections included: section 1: socio-demographic data, section 2: the 24-hour diet recall questions, and section 3: the dietary diversity questionnaires (DDQ) were used for data collection. The data obtained were assessed with descriptive analysis, a One-Way Analysis of Variance (ANOVA) test, and a One-Sample T-Test. Results: There was no significant association (p>0.05) between income status and diet diversity among IIUM Kuantan students. The total calorie intake for female and male students did not meet the energy requirement according to Recommended Nutrient Intakes (RNI) 2017, with p<0.001 for both genders. Conclusions: It can be concluded that students’ income status is not associated with their diet diversity. The female and male university students in the IIUM Kuantan campus consumed less energy than recommended by guidelines. Therefore, high or low-income students can have a limited or very diverse diet. Future studies should examine the elements that affect the variety of their diets.